Performance and Emission Characteristics of an Engine Fueled with Mangrove Bioethanol”“Gasoline Blends - Syarifudin Syarifudin; Eflita Yohana; Muchammad Muchammad; Suhartana Suhartana (Automotive Experiences, 2025)
Alternative fuels are a primary solution to address fuel scarcity and the adverse effects of fossil fuels, such as air pollution. Bioethanol is notable for its simple production process and the use of flexible raw materials, although it is often derived from crops used in food production. Mangrove bioethanol, however, is produced from Rhizophora mucronata mangrove fruit, which is abundant, rich in carbohydrates, and not part of the human food chain. This study aimed to evaluate the use of mangrove bioethanol as a biofuel on engine performance and emission reduction in gasoline engines. Laboratory-based experiments were conducted using mangrove bioethanol blends at concentrations of 5% (GE5) and 10% (GE10). Pure gasoline (G100) served as the baseline for comparison. The results showed that GE10 delivered better engine performance and lower emissions than both G100 and GE5, likely due to its high octane rating and oxygen content. Performance improvements with GE10 included increases of 7.89% in brake torque (BT) and brake power (BP), 47.55% in brake thermal efficiency (BTE), and 20.33% in exhaust gas temperature (EGT), along with a 98% reduction in brake specific fuel consumption (BSFC). In terms of emissions, GE10 led to reductions in carbon monoxide (CO) and hydrocarbon (HC) emissions by 43.56% and 36.54%, respectively, while carbon dioxide (COâ‚‚) emissions increased by 59.42%.